Implementation of an Integrated Problem Based Learning Model in Acid-Base Material - Winda Lestari Saragih; Ratu Evina Dibyantini (Universitas Negeri Medan, 2024)
This research was carried out on the basis of the dominance of the use of lecture methods and the lack of use of learning tools in learning especially on Acid-Base material at SMAN 1 Purba. This research aims to (1) know significant influence between prior knowledge and LKPD on learning outcomes. (2) knowing the difference in learning outcomes between high initial knowledge and low initial knowledge. The population of this study were all class XI SMAN 1 Purba consisting of 3 classes by determining 1 class as the research sample, namely class XI-1 using purposive sampling techniques. This research uses multiple linear regression test and Independent Sample t-Test. Based on data analysis, values are obtained the average EPA is 78.24; 86.00; 72.62, average LKPD value is 78.82; 87.06; 74.12 and the average EHB value is 79.26; 88.97; 82.47. Observation data from the observation sheet the average value obtained was 82.06; 87.57; 82.50. Based on the multiple linear regression test, there is a significant influence between initial knowledge and LKPD on learning outcomes. Results Independent Sample t-Test There is a significant difference in learning outcome scores between students with initially high ability and students with low initial ability.